Probabilistic Fiscal Monitoring and Reverse Threshold Analysis of Türkiye’s Public Health Administration under High Inflation - İlknur Arslan Aras (Journal of International Health Sciences and Management, 2026)
Background: Public health administrations face correlated revenue, labour-cost and supply-price uncertainty, yet consolidated financial statements are usually interpreted through retrospective point estimates. This study evaluates an integrated decision-support framework for fiscal monitoring without treating accounting outcomes as measures of managerial performance. Materials and Methods: The Turkish Ministry of Health’s comparable 2024–2025 consolidated accrual statements were analysed. Reported and researcher-defined core balances were reconciled; concentration was measured; and the change in core coverage was decomposed using a two-factor Shapley method. Three conditional 2026 scenarios were assessed using 100,000 correlated beta-PERT draws per scenario with Latin hypercube sampling. Outcomes included coverage, Fiscal-at-Risk, expected shortfall, reverse revenue thresholds and global sensitivity. Results: Core coverage increased from 47.75% to 49.49%, although the core financing gap rose from TRY 635.7 billion to TRY 867.0 billion. Revenue growth contributed 18.86 percentage points to coverage, while expenditure growth offset 17.12 points. Labour-related costs represented 67.28% of 2025 core expenditure, and one revenue class represented 83.68% of gross revenue. In the baseline scenario, the median modelled gap was TRY 1,205.6 billion and Fiscal-at-Risk at 95% was TRY 1,324.5 billion. Under managed disinflation, coverage improved in most draws while the nominal gap widened. Conclusions: The framework reveals a practically important divergence between proportional coverage and absolute financing need and converts static accounts into transparent, scenario-conditioned risk measures. Outputs are not official forecasts, causal estimates or audit findings.